THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE AND PERCEPTION OF THE USE OF TRADITIONAL MEDICINE IN THE PEOPLE OF KLATEN CITY IN 2022 - Tista Ayu Fortuna; Arifah Sri Wahyuni; Nadya Tiara Putri (Jurnal Farmasi Sains dan Praktis, 2023)
The use of traditional medicine in today's society is increasing with labels "back to nature" which is realized through the utilization of Indonesia's natural potential. Based on an incidental survey study in Klaten City, the affecting factor the use of traditional medicine in this region is knowledge and perception. Public knowledge related to the utilization of traditional medicine is assumed to be lacking because of the assumption that traditional medicine is much safer than chemical drugs. There is an assumption based on the side effects of traditional medicine being lower than chemical drugs. This study aims to assess the contribution of perception and knowledge to the use of traditional medicine. The research uses a cross-sectional study and the data collection instruments through questionnaires. The sampling technique used was purposive sampling with a total of 1089 respondents. Data collection used a questionnaire instrument whose results were analyzed using the Chi-Square statistical test. From these results can be concluded that types of knowledge involve definitions, type, efficacy, side effects, how to use, perceptions, convenience, currentness, and policy that can affect the use of traditional medicine. The results of data analysis show that the contribution of knowledge and perception to the use of traditional medicine has a coefficient of determination of 0.742